A renewable fiber nonwoven fabric and a method for manufacturing the same
By adding modified chitosan and a modified finishing agent to the spinning solution, the problems of decreased antibacterial properties and pilling of renewable fiber nonwoven fabrics after multiple washes were solved, and the wash-resistant antibacterial and anti-pilling properties of nonwoven fabrics were achieved.
Patent Information
- Application Number
- CN202410520376.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2026-03-20
- Estimated Expiration
- 2044-04-28
AI Technical Summary
Existing renewable fiber nonwoven fabrics suffer from decreased antibacterial properties and pilling after repeated washing.
By adding modified chitosan to the spinning solution and using a modifying agent to finish the viscose fiber nonwoven fabric, the modified chitosan and viscose fiber spinning solution are mixed and then spun, drawn, washed, web-laid and hydroentangled. Subsequently, the fabric is soaked in the modifying solution and pre-dried and baked to form hydrogen bonds and chemical bonds between the modifying agent and the fiber.
This technology enables nonwoven fabrics to retain good antibacterial properties and anti-pilling ability even after multiple washes. The modified finishing agent undergoes disulfide bond recombination after high-temperature treatment, reducing the loss of mechanical properties.
Smart Images

Figure BDA0004814896100000131
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of non-woven fabrics, in particular to a renewable fiber non-woven fabric and a preparation method thereof. BACKGROUND
[0002] Regenerated cellulose fibers have been widely used in people's daily life, and different preparation methods can divide the regenerated cellulose fibers into viscose fibers, Tencel, ionic liquid regenerated fibers, and cuprammonium fibers. Among them, the fabric using viscose fibers as raw materials has excellent moisture absorption, air permeability, antistatic property and good mechanical properties, and is widely used in textiles, clothing, medical care, health care and other fields, and plays an important role in people's life and production.
[0003] However, due to the characteristics of viscose fibers, its application in related fields is limited. For example, good moisture absorption makes the fabric prone to moisture, which causes bacteria to breed, thereby limiting its application in some fields. In order to make viscose fiber products have antibacterial properties, the fiber products are usually soaked in antibacterial finishing agents for antibacterial modification, but the antibacterial performance will decrease after multiple washes, thereby failing to meet the use requirements. At the same time, viscose fiber products are prone to pilling after being subjected to friction during production and wearing, which not only affects the appearance and quality of the fabric, but also reduces the beauty and hand feeling of the fabric. The commonly used silicone oil finishing agent has poor adsorption performance with viscose fiber products, and the finishing agent falls off after multiple washes, resulting in pilling of viscose fiber products. SUMMARY
[0004] The purpose of the present application is to provide a renewable fiber non-woven fabric and a preparation method thereof, which solves the problems of decreased antibacterial performance and pilling after multiple washes of the existing renewable fiber non-woven fabric.
[0005] The purpose of the present application can be achieved by the following technical solutions:
[0006] A renewable fiber non-woven fabric is prepared by the following steps: step S1: mixing viscose spinning dope and modified chitosan, and sending them to a spinning machine for spinning, and then passing through a coagulation bath, followed by drawing, washing, and obtaining viscose fibers; laying the viscose fibers, water jet reinforcing, and drying to obtain a viscose fiber non-woven fabric; the mass fraction of cellulose I in the viscose fiber spinning dope is 65%, and the mass ratio of modified chitosan to cellulose I in the viscose fiber spinning dope is 15-20:100;
[0007] Step S2: mixing the modified finishing agent with deionized water to prepare a modified finishing liquid, soaking the viscose fiber non-woven fabric in the modified finishing liquid, double-dipping and double-rolling with a mangle, bath ratio 1:10, controlling the rolling rate at 80%, pre-drying at 90℃ for 20 minutes, and baking at 160℃ for 5 minutes to prepare a renewable fiber non-woven fabric, the mass concentration of the modified finishing liquid being 80g / L;
[0008] The modified chitosan is prepared by the following steps:
[0009] Step A1: mixing chitosan and acetic acid solution, stirring under nitrogen protection at a stirring speed of 120-180rpm and room temperature, adding hydrogen peroxide and ascorbic acid, reacting for 30-40min, adding epigallocatechin gallate, and continuing to react for 24h to prepare grafted chitosan;
[0010] The volume fraction of the acetic acid solution is 1%, the molar concentration of the hydrogen peroxide solution is 1mol / L, and the dosage ratio of chitosan, hydrogen peroxide, ascorbic acid and epigallocatechin gallate is 0.5-1g:10-14mL:0.05-0.07g:0.5-0.8g;
[0011] During the reaction process, in the acetic acid solution, ascorbic acid reacts with hydrogen peroxide to generate ascorbic acid free radicals, which are mediated to react with the hydroxyl and amino groups in chitosan to generate chitosan molecular free radicals, which further react with the hydroxyl groups in epigallocatechin gallate to graft epigallocatechin gallate onto chitosan to prepare grafted chitosan;
[0012] Step A2: mixing grafted chitosan, histidine and acetic acid solution, reacting at a stirring speed of 240-300rpm and a temperature of 60℃ for 5-6h to prepare histidine chitosan, mixing histidine chitosan, benzyl bromide and dimethylformamide, stirring at a stirring speed of 120-180rpm and room temperature, adding potassium carbonate and potassium iodide, and reacting for 24h to prepare benzyl-protected chitosan;
[0013] The volume fraction of the acetic acid solution is 1%, and the dosage ratio of grafted chitosan and histidine is 1-1.4g:0.3-0.4g, and the dosage ratio of histidine chitosan, benzyl bromide, potassium carbonate and potassium iodide is 1.2-1.6g:2-2.4g:2g:1g;
[0014] During the reaction process, the ortho-phenolic hydroxyl groups in grafted chitosan react with the amino groups in histidine to form a histidine salt structure to prepare histidine chitosan, and then the unreacted ortho-phenolic hydroxyl groups are protected by benzyl bromide under the action of potassium carbonate and potassium iodide to avoid the participation of the ortho-phenolic hydroxyl groups in the subsequent complexation process with silver ions to prepare benzyl-protected chitosan;
[0015] Step A3: mixing benzyl-protected chitosan, silver nitrate solution and deionized water, under the condition of stirring rate of 800-900 rpm and temperature of 50℃, reaction for 30 min to prepare complex silver chitosan, mixing complex silver chitosan and dichloromethane, under the condition of stirring rate of 300-400 rpm and room temperature, stirring and adding boron trifluoride ether, reaction for 20-30 min to prepare modified chitosan;
[0016] The molar concentration of the silver nitrate solution is 0.25 mol / L, the dosage ratio of benzyl-protected chitosan to silver nitrate solution is 1.4-1.8 g:10-12 mL, and the dosage ratio of complex silver chitosan to boron trifluoride ether is 1.3-1.6 g:15-18 mL;
[0017] During the reaction, the imidazole group and carboxyl group in the histidine structure in the benzyl-protected chitosan can coordinate with silver ions to form a complex, thereby preparing complex silver chitosan, and then adding boron trifluoride ether to deprotect the benzyl group to form ortho phenolic hydroxyl group, thereby preparing modified chitosan;
[0018] The modified finishing agent is prepared by the following steps:
[0019] Step B1: mixing mercaptopropyl methyl dimethoxy silane, decamethylcyclopentasiloxane and hexamethyldisiloxane, under the condition of stirring rate of 200-300 rpm and temperature of 80℃, stirring and adding trifluoromethanesulfonic acid and deionized water, reaction for 6-8 h to prepare mercapto silicone oil, mixing mercapto silicone oil, itaconic acid, benzoin dimethyl ether and tetrahydrofuran, under the condition of 100 W ultraviolet light irradiation, stirring rate of 120-180 rpm and room temperature, reaction for 4-5 h to prepare carboxyl silicone oil;
[0020] The dosage ratio of mercaptopropyl methyl dimethoxy silane, decamethylcyclopentasiloxane, hexamethyldisiloxane and trifluoromethanesulfonic acid is 0.4-0.5 mol:0.8-1 mol:0.01 mol:7-8 g, and the dosage ratio of mercapto silicone oil, itaconic acid and benzoin dimethyl ether is 7-8 g:0.06 mol:0.2 g;
[0021] During the reaction, mercapto silicone oil is prepared by hydrolytic condensation of mercaptopropyl methyl dimethoxy silane and decamethylcyclopentasiloxane, and then the mercapto group in the mercapto silicone oil reacts with the double bond in the itaconic acid under the condition of benzoin dimethyl ether and ultraviolet light to form a thioether bond, thereby preparing carboxyl silicone oil;
[0022] Step B2: mixing carboxyl silicone oil, bis(2-hydroxyethyl) disulfide, propylene glycol and succinic acid, under the condition of nitrogen protection, stirring rate of 300-400 rpm and temperature of 160℃, stirring and adding tetrabutyl titanate and hydroquinone, reaction for 2-3 h, vacuum extraction to 0.09 MPa, and continuing to react for 5-6 h to prepare polyester silicone oil.
[0023] Carboxyl silicone oil, bis (2-hydroxyethyl) disulfide, propylene glycol, succinic acid, tetrabutyl titanate and hydroquinone dosage ratio is 8-10g: 0.08-0.1mol: 0.1-0.12mol: 0.1mol: 0.01g: 0.01g;
[0024] During the reaction, the carboxyl groups in the carboxyl silicone oil and succinic acid react with the hydroxyl groups in bis (2-hydroxyethyl) disulfide and propylene glycol to form ester groups, and at the same time, due to the excess of alcohol, a polyester silicone oil capped with hydroxyl groups is prepared;
[0025] Step B3: Mix 4, 4' dicyclohexyl methane diisocyanate, polyester silicone oil and acetone, under the condition of nitrogen protection, stirring rate of 400-500 rpm, temperature of 50℃, stir and add dibutyltin dilaurate, react for 2h, heat to 60℃ and add methyl ethyl ketoxime, continue to react for 1-1.5h, prepare modified finishing agent;
[0026] 4, 4' dicyclohexyl methane diisocyanate, polyester silicone oil, dibutyltin dilaurate and methyl ethyl ketoxime dosage ratio is 0.06-0.08mol: 14-16g: 0.1g: 0.1mol;
[0027] During the reaction, 4, 4' dicyclohexyl methane diisocyanate reacts with the terminal hydroxyl groups in the polyester silicone oil to form urethane groups, and is capped with isocyanate groups, and then reacts with methyl ethyl ketoxime to cap the terminal isocyanate groups, to prepare a modified finishing agent;
[0028] The application discloses a renewable fiber non-woven fabric and a preparation method thereof, and the renewable non-woven fabric has good washing-resistant and antibacterial performance by adding modified chitosan in a spinning dope, and the non-woven fabric has washing-resistant and anti-pilling performance by using a modified finishing agent for finishing. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the application.
[0030] Embodiment 1
[0031] The modified chitosan is prepared by the following steps:
[0032] Step A1: mixing commercially available blue season biological chitosan and acetic acid solution, stirring under nitrogen protection at a stirring rate of 120 rpm at room temperature, adding hydrogen peroxide and ascorbic acid, reacting for 40 min, adding epigallocatechin gallate, and continuing to react for 24 h to prepare grafted chitosan;
[0033] The volume fraction of the acetic acid solution is 1%, the molar concentration of the hydrogen peroxide solution is 1 mol / L, and the dosage ratio of chitosan, hydrogen peroxide, ascorbic acid and epigallocatechin gallate is 0.5 g:10 mL:0.05 g:0.5 g;
[0034] Step A2: mixing grafted chitosan, histidine and acetic acid solution, reacting for 6 h at a stirring rate of 240 rpm at a temperature of 60°C to prepare histidine chitosan, mixing histidine chitosan, benzyl bromide and dimethylformamide, stirring at a stirring rate of 120 rpm at room temperature, adding potassium carbonate and potassium iodide, and reacting for 24 h to prepare benzyl-protected chitosan;
[0035] The volume fraction of the acetic acid solution is 1%, the dosage ratio of grafted chitosan and histidine is 1 g:0.3 g, and the dosage ratio of histidine chitosan, benzyl bromide, potassium carbonate and potassium iodide is 1.2 g:2 g:2 g:1 g;
[0036] Step A3: mixing benzyl-protected chitosan, silver nitrate solution and deionized water, reacting for 30 min at a stirring rate of 800 rpm at a temperature of 50°C to prepare complex silver chitosan, mixing complex silver chitosan and dichloromethane, stirring at a stirring rate of 300 rpm at room temperature, adding boron trifluoride ether, and reacting for 30 min to prepare modified chitosan;
[0037] The molar concentration of the silver nitrate solution is 0.25 mol / L, the dosage ratio of benzyl-protected chitosan and silver nitrate solution is 1.4 g:10 mL, and the dosage ratio of complex silver chitosan and boron trifluoride ether is 1.3 g:15 mL.
[0038] Example 2
[0039] The modified chitosan is prepared by the following steps:
[0040] Step A1: mixing commercially available blue season biological chitosan and acetic acid solution, stirring under nitrogen protection at a stirring rate of 180 rpm at room temperature, adding hydrogen peroxide and ascorbic acid, reacting for 30 min, adding epigallocatechin gallate, and continuing to react for 24 h to prepare grafted chitosan;
[0041] The volume fraction of acetic acid solution is 1%, the molar concentration of hydrogen peroxide solution is 1 mol / L, and the dosage ratio of chitosan, hydrogen peroxide, ascorbic acid and epigallocatechin gallate is 0.8 g: 14 mL: 0.07 g: 0.8 g;
[0042] Step A2: The grafted chitosan, histidine and acetic acid solution are mixed, and histidine chitosan is prepared by stirring at a stirring rate of 300 rpm and at a temperature of 60 DEG C for 5 h. The histidine chitosan, benzyl bromide and dimethylformamide are mixed, and benzyl-protected chitosan is prepared by stirring at a stirring rate of 180 rpm at room temperature, stirring and adding potassium carbonate and potassium iodide, and reacting for 24 h.
[0043] The volume fraction of acetic acid solution is 1%, the dosage ratio of grafted chitosan and histidine is 1.2 g: 0.4 g, and the dosage ratio of histidine chitosan, benzyl bromide, potassium carbonate and potassium iodide is 1.4 g: 2.4 g: 2 g: 1 g.
[0044] Step A3: The benzyl-protected chitosan, silver nitrate solution and deionized water are mixed, and complex silver chitosan is prepared by stirring at a stirring rate of 900 rpm and at a temperature of 50 DEG C for 30 min. The complex silver chitosan and dichloromethane are mixed, and modified chitosan is prepared by stirring at a stirring rate of 400 rpm at room temperature, stirring and adding boron trifluoride ether, and reacting for 20 min.
[0045] The molar concentration of silver nitrate solution is 0.25 mol / L, the dosage ratio of benzyl-protected chitosan and silver nitrate solution is 1.6 g: 12 mL, and the dosage ratio of complex silver chitosan and boron trifluoride ether is 1.6 g: 18 mL.
[0046] Example 3
[0047] The modified chitosan is prepared by the following steps:
[0048] Step A1: The commercially available blue season biological chitosan and acetic acid solution are mixed, and the grafted chitosan is prepared by stirring at a stirring rate of 180 rpm at room temperature under nitrogen protection, stirring and adding hydrogen peroxide and ascorbic acid, and reacting for 40 min. Epigallocatechin gallate is added, and the reaction is continued for 24 h.
[0049] The volume fraction of acetic acid solution is 1%, the molar concentration of hydrogen peroxide solution is 1 mol / L, and the dosage ratio of chitosan, hydrogen peroxide, ascorbic acid and epigallocatechin gallate is 1 g: 14 mL: 0.07 g: 0.8 g.
[0050] Step A2: grafting chitosan, histidine and acetic acid solution were mixed, under the condition of stirring rate 300 rpm and temperature 60℃, reaction for 6h, histidine chitosan was prepared, histidine chitosan, benzyl bromide and dimethylformamide were mixed, under the condition of stirring rate 180 rpm and room temperature, stirring and adding potassium carbonate and potassium iodide, reaction for 24h, benzyl protected chitosan was prepared;
[0051] The volume fraction of acetic acid solution was 1%, the amount ratio of grafting chitosan and histidine was 1.4g:0.4g, the amount ratio of histidine chitosan, benzyl bromide, potassium carbonate and potassium iodide was 1.6g:2.4g:2g:1g;
[0052] Step A3: benzyl protected chitosan, silver nitrate solution and deionized water were mixed, under the condition of stirring rate 900 rpm and temperature 50℃, reaction for 30min, complex silver chitosan was prepared, complex silver chitosan and dichloromethane were mixed, under the condition of stirring rate 400 rpm and room temperature, stirring and adding boron trifluoride ether, reaction for 30min, modified chitosan was prepared;
[0053] The molar concentration of silver nitrate solution was 0.25mol / L, the amount ratio of benzyl protected chitosan and silver nitrate solution was 1.8g:12mL, the amount ratio of complex silver chitosan and boron trifluoride ether was 1.6g:18mL.
[0054] Example 4
[0055] The modified finishing agent was prepared by the following steps:
[0056] Step B1: mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane and hexamethyldisiloxane were mixed, under the condition of stirring rate 200 rpm and temperature 80℃, stirring and adding triflic acid and deionized water, reaction for 8h, mercaptosilicone oil was prepared, mercaptosilicone oil, itaconic acid, benzoin dimethyl ether and tetrahydrofuran were mixed, under the condition of 100W ultraviolet light irradiation, stirring rate 120 rpm and room temperature, reaction for 5h, carboxyl silicone oil was prepared;
[0057] The amount ratio of mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane, hexamethyldisiloxane and triflic acid was 0.4mol:0.8mol:0.01mol:7g, the amount ratio of mercaptosilicone oil, itaconic acid and benzoin dimethyl ether was 7g:0.06mol:0.2g;
[0058] Step B2: carboxyl silicone oil, bis(2-hydroxyethyl) disulfide, propylene glycol and succinic acid were mixed, under the condition of nitrogen protection, stirring rate 300 rpm and temperature 160℃, stirring and adding tetrabutyl titanate and hydroquinone, reaction for 3h, vacuum extraction to 0.09MPa, continue to react for 6h, polyester silicone oil was prepared;
[0059] Carboxyl silicone oil, bis (2-hydroxyethyl) disulfide, propylene glycol, succinic acid, tetrabutyl titanate and hydroquinone were mixed in a ratio of 8 g: 0.08 mol: 0.1 mol: 0.1 mol: 0.01 g: 0.01 g;
[0060] Step B3: 4, 4' dicyclohexyl methane diisocyanate, polyester silicone oil and acetone were mixed, stirred under nitrogen protection, the stirring rate was 400 rpm, the temperature was 50℃, dibutyltin dilaurate was added, reacted for 2h, the temperature was increased to 60℃, methyl ethyl ketoxime was added, and the reaction was continued for 1.5h to prepare the modified finishing agent;
[0061] 4, 4' dicyclohexyl methane diisocyanate, polyester silicone oil, dibutyltin dilaurate and methyl ethyl ketoxime were mixed in a ratio of 0.06 mol: 16 g: 0.1 g: 0.1 mol.
[0062] Example 5
[0063] The modified finishing agent was prepared by the following steps:
[0064] Step B1: Mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane and hexamethyldisiloxane were mixed, stirred at a stirring rate of 300 rpm and a temperature of 80℃, trifluoromethanesulfonic acid and deionized water were added, reacted for 6h to prepare mercaptosilicone oil, and the mercaptosilicone oil, itaconic acid, benzoin dimethyl ether and tetrahydrofuran were mixed, irradiated with 100W ultraviolet light, stirred at a stirring rate of 180 rpm and room temperature, and reacted for 4h to prepare carboxyl silicone oil;
[0065] Mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane, hexamethyldisiloxane and trifluoromethanesulfonic acid were mixed in a ratio of 0.5 mol: 0.8 mol: 0.01 mol: 8 g, and mercaptosilicone oil, itaconic acid and benzoin dimethyl ether were mixed in a ratio of 8 g: 0.06 mol: 0.2 g;
[0066] Step B2: Carboxyl silicone oil, bis (2-hydroxyethyl) disulfide, propylene glycol and succinic acid were mixed, stirred under nitrogen protection, the stirring rate was 400 rpm, the temperature was 160℃, tetrabutyl titanate and hydroquinone were added, reacted for 2h, vacuumized to 0.09 MPa, and the reaction was continued for 5h to prepare polyester silicone oil;
[0067] Carboxyl silicone oil, bis (2-hydroxyethyl) disulfide, propylene glycol, succinic acid, tetrabutyl titanate and hydroquinone were mixed in a ratio of 10 g: 0.08 mol: 0.1 mol: 0.1 mol: 0.01 g: 0.01 g;
[0068] Step B3: 4,4'-dicyclohexylmethane diisocyanate, polyester silicone oil and acetone were mixed, stirred and dibutyltin dilaurate was added under nitrogen protection at a stirring rate of 500 rpm and a temperature of 50°C, reacted for 2 h, warmed to 60°C and methyl ethyl ketoxime was added, and reacted for 1.5 h to obtain the modified finishing agent;
[0069] 4,4'-dicyclohexylmethane diisocyanate, polyester silicone oil, dibutyltin dilaurate and methyl ethyl ketoxime were used in a ratio of 0.06 mol: 16 g: 0.1 g: 0.1 mol.
[0070] Example 6
[0071] The modified finishing agent was prepared by the following steps:
[0072] Step B1: Mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane and hexamethyldisiloxane were mixed, stirred and trifluoromethanesulfonic acid and deionized water were added under a stirring rate of 300 rpm and a temperature of 80°C, reacted for 8 h to obtain mercaptosilicone oil, and the mercaptosilicone oil, itaconic acid, benzoin dimethyl ether and tetrahydrofuran were mixed, irradiated with 100W ultraviolet light, stirred at a stirring rate of 180 rpm and reacted for 4-5 h at room temperature to obtain carboxyl silicone oil;
[0073] Mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane, hexamethyldisiloxane and trifluoromethanesulfonic acid were used in a ratio of 0.5 mol: 1 mol: 0.01 mol: 8 g, and the mercaptosilicone oil, itaconic acid and benzoin dimethyl ether were used in a ratio of 8 g: 0.06 mol: 0.2 g;
[0074] Step B2: Carboxyl silicone oil, bis(2-hydroxyethyl) disulfide, propylene glycol and succinic acid were mixed, stirred and tetrabutyl titanate and hydroquinone were added under nitrogen protection at a stirring rate of 400 rpm and a temperature of 160°C, reacted for 3 h, vacuumed to 0.09 MPa and reacted for 6 h to obtain polyester silicone oil;
[0075] Carboxyl silicone oil, bis(2-hydroxyethyl) disulfide, propylene glycol, succinic acid, tetrabutyl titanate and hydroquinone were used in a ratio of 10 g: 0.1 mol: 0.12 mol: 0.1 mol: 0.01 g: 0.01 g;
[0076] Step B3: 4,4'-dicyclohexylmethane diisocyanate, polyester silicone oil and acetone were mixed, stirred and dibutyltin dilaurate was added under nitrogen protection at a stirring rate of 500 rpm and a temperature of 50°C, reacted for 2 h, warmed to 60°C and methyl ethyl ketoxime was added, and reacted for 1.5 h to obtain the modified finishing agent;
[0077] 4,4'-dicyclohexylmethane diisocyanate, polyester silicone oil, dibutyl tin dilaurate and methyl ethyl ketoxime in a ratio of 0.08 mol: 16 g: 0.1 g: 0.1 mol.
[0078] Example 7
[0079] A renewable fiber non-woven fabric is prepared by the following steps: step S1: mixing viscose spinning dope with the modified chitosan of Example 1, and sending it to a spinning machine for spinning, passing through a coagulation bath, then drawing, washing, and obtaining viscose fibers; laying the viscose fibers, water jet reinforcing, and drying to obtain a viscose fiber non-woven fabric; the mass fraction of alpha cellulose in the viscose fiber spinning dope is 65%, and the mass ratio of modified chitosan to alpha cellulose in the viscose fiber spinning dope is 15:100;
[0080] Step S2: mixing the modified finishing agent of Example 4 with deionized water to obtain a modified finishing liquid; soaking the viscose fiber non-woven fabric in the modified finishing liquid, and using a rolling machine for double immersion and double rolling with a bath ratio of 1:10 and a control rolling rate of 80%; pre-drying at 90°C for 20 min and baking at 160°C for 5 min to obtain a renewable fiber non-woven fabric; the mass concentration of the modified finishing liquid is 80 g / L.
[0081] Example 8
[0082] A renewable fiber non-woven fabric is prepared by the following steps: step S1: mixing viscose spinning dope with the modified chitosan of Example 2, and sending it to a spinning machine for spinning, passing through a coagulation bath, then drawing, washing, and obtaining viscose fibers; laying the viscose fibers, water jet reinforcing, and drying to obtain a viscose fiber non-woven fabric; the mass fraction of alpha cellulose in the viscose fiber spinning dope is 65%, and the mass ratio of modified chitosan to alpha cellulose in the viscose fiber spinning dope is 20:100;
[0083] Step S2: mixing the modified finishing agent of Example 5 with deionized water to obtain a modified finishing liquid; soaking the viscose fiber non-woven fabric in the modified finishing liquid, and using a rolling machine for double immersion and double rolling with a bath ratio of 1:10 and a control rolling rate of 80%; pre-drying at 90°C for 20 min and baking at 160°C for 5 min to obtain a renewable fiber non-woven fabric; the mass concentration of the modified finishing liquid is 80 g / L.
[0084] Example 9
[0085] A renewable fiber non-woven fabric is prepared by the following steps: step S1: mixing viscose spinning dope with the modified chitosan of Example 3, and sending it to a spinning machine for spinning, passing through a coagulation bath, then drawing, washing, and obtaining viscose fibers; laying the viscose fibers, water jet reinforcing, and drying to obtain a viscose fiber non-woven fabric; the mass fraction of alpha cellulose in the viscose fiber spinning dope is 65%, and the mass ratio of modified chitosan to alpha cellulose in the viscose fiber spinning dope is 20:100;
[0086] Step S2: The modified finishing agent of Example 6 was mixed with deionized water to prepare a modified finishing liquid, and the viscose fiber non-woven fabric was soaked in the modified finishing liquid, and was double-dipped and double-rolled by a mangle with a bath ratio of 1:10, the rolling rate was controlled at 80%, and was pre-dried at 90°C for 20 min, and was baked at 160°C for 5 min, to prepare a renewable fiber non-woven fabric, and the mass concentration of the modified finishing liquid was 80 g / L.
[0087] Comparative Example 1
[0088] The present comparative example was compared with Example 9, and the complex silver chitosan in the preparation process of the modified chitosan was replaced by benzyl-protected chitosan, and the other steps were the same.
[0089] Comparative Example 2
[0090] The present comparative example was compared with Example 9, and the complex silver chitosan in the preparation process of the modified chitosan was replaced by benzyl-protected chitosan, and the other steps were the same.
[0091] Comparative Example 3
[0092] The present comparative example was compared with Example 9, and the modified finishing agent was replaced by a commercially available F-ECO finishing agent, and the other steps were the same.
[0093] Comparative Example 4
[0094] The present comparative example was compared with Example 9, and the methyl ethyl ketone oxime in the preparation process of the modified finishing agent was removed, and the other steps were the same.
[0095] Comparative Example 5
[0096] The present comparative example was compared with Example 9, and the bis(2-hydroxyethyl) disulfide in the preparation process of the modified finishing agent was replaced by propylene glycol, and the other steps were the same.
[0097] A renewable fiber non-woven fabric was prepared by using the modified finishing agent of Example 7, Example 8, Example 9, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5, and the renewable fiber non-woven fabric was cut into a sample and was washed 15 times according to GB / T20944.3-2008, and the antibacterial performance of the sample was tested; the renewable fiber non-woven fabric was cut into a sample with a diameter of 113 mm, and was raised 50 times and then was pilled 50 times under a pressure of 590 cN according to GB / T4802.1-2008, and the standard gray raised and pilled card was used for comparison, and the anti-raising and pilling performance of the sample was evaluated, and the anti-raising and pilling performance of the sample after being washed 15 times was tested; the renewable fiber non-woven fabric was cut into a sample with a size of 20 cm x 5 cm, and the clamping distance was set to 100 mm and the stretching speed was set to 100 mm / min, and the mechanical properties of the sample were tested according to GB / T3923.1-2013, and the test results are shown in the following table:
[0098]
[0099] From the results of the table, it can be seen that by comparing Example 7, Example 8 and Example 9 with Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5, in Comparative Example 1, the benzyl-protected chitosan is replaced by histidine chitosan in the preparation of the modified chitosan, and due to the complexation of the ortho-phenolic hydroxyl group of the modified chitosan with silver ions, the hydrogen bond connection between the modified chitosan and the viscose fiber is reduced, thereby causing a serious decline in the antibacterial performance after washing; in Comparative Example 2, the complex silver chitosan is replaced by benzyl-protected chitosan in the preparation of the modified chitosan, and due to the lack of complex silver ions, the antibacterial performance is seriously reduced; in Comparative Example 3, the modified finishing agent is replaced by a commercially available F-ECO finishing agent, and there is no chemical bond connection between the commercially available F-ECO finishing agent and the non-woven fabric, thereby causing a serious decline in the anti-pilling performance after washing; in Comparative Example 4, the methyl ethyl ketoxime is removed in the preparation process of the modified finishing agent, and due to the lack of isocyanate protecting groups, the modified finishing agent directly reacts with the non-woven fabric in the post-processing process without penetrating into the non-woven fabric, thereby causing a decline in the anti-pilling performance and the mechanical properties; in Comparative Example 5, the bis(2-hydroxyethyl) disulfide is replaced by propylene glycol in the preparation process of the modified finishing agent, and due to the lack of disulfide bonds, the non-woven fabric has a lot of mechanical property loss in the post-processing process.
[0100] In the description of the specification, the description of the terms "one embodiment", "an example", "a specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0101] The above is only an example and description of the concept of the present application, and those skilled in the art can make various modifications or supplements or use similar ways to replace the described specific embodiments, as long as they do not deviate from the concept of the invention or exceed the scope defined by the present claims, which shall be within the protection scope of the present application.
Claims
1. A method for preparing a renewable fiber nonwoven fabric, characterized in that: The viscose fiber is prepared by the following steps: Step S1: The viscose spinning solution is mixed with modified chitosan and fed into a spinning machine for spinning. After passing through a coagulation bath, it is stretched and washed to obtain viscose fiber. The viscose fiber is then laid into a web, hydroentangled and dried to obtain viscose fiber nonwoven fabric. The mass fraction of methyl cellulose in the viscose fiber spinning solution is 65%, and the mass ratio of modified chitosan to methyl cellulose in the viscose fiber spinning solution is 15-20:
100. Step S2: Mix the modifying agent with deionized water to prepare a modified finishing solution. Immerse the viscose fiber nonwoven fabric in the modified finishing solution, and perform two dips and two nips using a nipper car. The liquor ratio is 1:10, and the nipper rate is controlled at 80%. Pre-dry at 90℃ for 20 minutes and bake at 160℃ for 5 minutes to obtain a renewable fiber nonwoven fabric. The mass concentration of the modified finishing solution is 80 g / L. The modified finishing agent is prepared by the following steps: Step B1: Mix mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane and hexamethyldisiloxane, stir at 200-300 rpm and 80°C, add trifluoromethanesulfonic acid and deionized water, react for 6-8 h to obtain mercaptosilicone oil. Mix mercaptosilicone oil, itaconic acid, benzoin dimethyl ether and tetrahydrofuran, irradiate with 100W ultraviolet light, stir at 120-180 rpm and at room temperature for 4-5 h to obtain carboxylsilicone oil. Step B2: Mix carboxylated silicone oil, bis(2-hydroxyethyl) disulfide, propylene glycol and succinic acid. Under nitrogen protection, with a stirring speed of 300-400 rpm and a temperature of 160℃, stir and add tetrabutyl titanate and hydroquinone. React for 2-3 hours, then evacuate to 0.09 MPa and continue the reaction for 5-6 hours to obtain polyester silicone oil. Step B3: Mix 4,4'-dicyclohexylmethane diisocyanate, polyester silicone oil and acetone. Under nitrogen protection, with a stirring speed of 400-500 rpm and a temperature of 50°C, stir and add dibutyltin dilaurate. React for 2 hours, then raise the temperature to 60°C and add methyl ethyl ketone oxime. Continue the reaction for 1-1.5 hours to obtain the modified finishing agent.
2. The method for preparing a renewable fiber nonwoven fabric according to claim 1, characterized in that: The modified chitosan was prepared through the following steps: Step A1: Mix chitosan and acetic acid solution, stir at 120-180 rpm under nitrogen protection at room temperature, add hydrogen peroxide and ascorbic acid, react for 30-40 min, add epigallocatechin gallate, and continue the reaction for 24 h to obtain grafted chitosan. Step A2: Mix the grafted chitosan, histidine, and acetic acid solution, and react for 5-6 hours at a stirring speed of 240-300 rpm and a temperature of 60℃ to obtain histidine chitosan. Mix histidine chitosan, benzyl bromide, and dimethylformamide, and stir at a stirring speed of 120-180 rpm and at room temperature, while adding potassium carbonate and potassium iodide, and react for 24 hours to obtain benzyl protected chitosan. Step A3: Mix benzyl protected chitosan, silver nitrate solution and deionized water, and react for 30 min at a stirring speed of 800-900 rpm and a temperature of 50℃ to obtain complexed silver chitosan. Mix the complexed silver chitosan with dichloromethane, and stir at a stirring speed of 300-400 rpm and a temperature of room temperature, and add boron trifluoride diethyl ether. React for 20-30 min to obtain modified chitosan.
3. The method for preparing a renewable fiber nonwoven fabric according to claim 2, characterized in that: In step A1, the volume fraction of acetic acid solution is 1%, the molar concentration of hydrogen peroxide solution is 1 mol / L, and the ratio of chitosan, hydrogen peroxide, ascorbic acid and epigallocatechin gallate is 0.5-1 g: 10-14 mL: 0.05-0.07 g: 0.5-0.8 g.
4. The method for preparing a renewable fiber nonwoven fabric according to claim 2, characterized in that: In step A2, the volume fraction of the acetic acid solution is 1%, the ratio of grafted chitosan to histidine is 1-1.4g:0.3-0.4g, and the ratio of histidine-chitosan, benzyl bromide, potassium carbonate, and potassium iodide is 1.2-1.6g:2-2.4g:2g:1g.
5. The method for preparing a renewable fiber nonwoven fabric according to claim 2, characterized in that: In step A3, the molar concentration of silver nitrate solution is 0.25 mol / L, the ratio of benzyl protected chitosan to silver nitrate solution is 1.4-1.8 g: 10-12 mL, and the ratio of complexed silver chitosan to boron trifluoride ether is 1.3-1.6 g: 15-18 mL.
6. The method for preparing a renewable fiber nonwoven fabric according to claim 1, characterized in that: In step B1: the ratio of mercaptopropylmethyldimethoxysilane, decamethylcyclopentasiloxane, hexamethyldisiloxane and trifluoromethanesulfonic acid is 0.4-0.5 mol: 0.8-1 mol: 0.01 mol: 7-8 g; the ratio of mercaptosilicone oil, itaconic acid and benzoin dimethyl ether is 7-8 g: 0.06 mol: 0.2 g.
7. The method for preparing a renewable fiber nonwoven fabric according to claim 1, characterized in that: In step B2, the ratio of carboxylated silicone oil, bis(2-hydroxyethyl) disulfide, propylene glycol, succinic acid, tetrabutyl titanate, and hydroquinone is 8-10g: 0.08-0.1mol: 0.1-0.12mol: 0.1mol: 0.01g: 0.01g.
8. The method for preparing a renewable fiber nonwoven fabric according to claim 1, characterized in that: In step B3: the ratio of 4,4'-dicyclohexylmethane diisocyanate, polyester silicone oil, dibutyltin dilaurate and methyl ethyl ketone oxime is 0.06-0.08 mol: 14-16 g: 0.1 g: 0.1 mol.
9. A renewable fiber nonwoven fabric, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.
Citation Information
Patent Citations
Nano-silver antibacterial composite decorated by modified chitosan, preparing method and application
CN104128602A
Preparation method of moisture-absorbing breathable bottom film
CN112626865A